Fibre-Multi-Object Spectrograph (FMOS) for Subaru telescope - Kimura, M; Maihara, T; Ohta, K; Iwamuro, F; Eto, S; Iino, M; Mochida, D; Shima, T; Karoji, H; Noumaru, J; Akiyama, M; Brezeski, J; et al. (2002)
The Fibre Multi-Object Spectrograph (FMOS) is a second-generation common-use instrument of the Subaru telescope. Under an international collaboration scheme of Japan, UK, and Australia, a realistic design of FMOS has been already in completion, and the fabrications of hardware components have been in progress. We present the overall design details together with the special features of FMOS subsystems, such as the prime focus corrector, the prime focus mechanical unit including fibre positioners, and the near-infrared spectrograph, etc.